Simulasi Website E-Commerce Toko Sujarwo Aluminium - Bayu Aditya Saputra; Liduina Asih Primandari; Indah Dwi Mumpuni (Dinamika Dotcom : Jurnal Pengembangan Manajemen Informatika dan Komputer, 2026)
Sujarwo Aluminum was founded by Mr. Eko Sujarwo. This shop focuses on the production of aluminum products in Nganjuk Regency. The products offered include windows, doors, frames, display cases, kitchen sets, shelves, cupboards and TV tables, with a production capacity of 2 to 10 projects per month. Currently, the product ordering process is still done conventionally via telephone or direct visit to the shop, but this method is considered less efficient by Mr. Eko Sujarwo. Conventional processes can cause several obstacles, such as the absence of Mr. Eko Sujarwo when contacted and the need for customers to come directly, causing the need for more efficient ordering methods. The proposed solution to overcome these obstacles is the development of an E-commerce website simulation using quantitative methods to facilitate online product ordering. This platform will increase sales efficiency, provide easily accessible product information, and reduce dependence on third-party platforms. The research results show that with the E-commerce website, customers can place orders in less than 1 hour compared to the previous time of 2-4 hours. Based on this research, an increase in efficiency of 50% -75% was obtained.